"Sehat Mantab" Health Awareness Program for the Community around the PT Putra Perkasa Abadi Mining - Muhammad Osaegi Restu Amrulloh; Shelvy Setia Innda; Aditya Ilham Prakasa; Endik Riyanto (Jurnal Indonesia Sosial Sains, 2024)
The SEHAT MANTAB program was initiated by PT. Putra Perkasa Abadi (PPA) is a comprehensive effort to improve the quality of public health around the mine. With a focus on increasing health awareness, HIV/AIDS prevention, education, and stunting prevention in children, this program runs from January 2023 to January 2024. Through activities such as "Clean Beaches and Free Health Checks" and HIV/AIDS education programs in schools, this program has succeeded in increasing public understanding of environmental cleanliness and HIV/AIDS risks. In addition, through the "Stunting Awareness" program, PPA has succeeded in reducing stunting rates in children through monitoring, evaluation, and the provision of PMT. Collaboration with stakeholders such as local governments and health workers is also the key to the success of this program. Through these various efforts, PPA hopes to create a healthier and more prosperous society and positively contribute to overcoming health problems in the mining area.